Polyether sulfone self-supporting ultrafiltration membrane capable of resisting biological pollution as well as preparation method and application of polyether sulfone self-supporting ultrafiltration membrane
The cellulose nanocrystals and antibacterial ions are fixed on the surface of the polyethersulfone membrane and the membrane pores in the prior art. The problem of hydrophilic materials and antibacterial ions in the prior art is solved, and the excellent hydrophilic properties and antibacterial pollution ability of the ultrafiltration membrane are achieved.
Patent Information
- Application Number
- CN202510622234.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-06-13
- Estimated Expiration
- 2045-05-15
AI Technical Summary
The prior art is difficult to act simultaneously on the surface of the self-supporting ultrafiltration membrane and the membrane pores, resulting in insufficient anti-pollution and hydrophilic properties of the membrane.
The cellulose nanocrystals and antibacterial ions are fixed on the surface of the polyethersulfone membrane and the membrane pores through polyphenol monomers to form a stable membrane structure, improving the hydrophilicity and antibacterial properties of the membrane.
The ultrafiltration membrane has achieved excellent hydrophilic properties and anti-biological pollution ability, making it highly efficient and stable application in water treatment or biological material treatment.
Smart Images

Figure CN120132606A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water treatment, and particularly relates to an anti-biofouling polyethersulfone self-supporting ultrafiltration membrane, a preparation method thereof, and an application thereof. Background Art
[0002] Membrane separation technology is a technology that separates one or more components in a mixture based on the principle of selective permeation of a membrane. This technology has the advantages of high efficiency, environmental protection, simple operation, etc., and thus has been widely used in the fields of water treatment, food and drug processing, biomedicine, chemical engineering, etc.
[0003] Membrane materials are the core components of membrane separation technology. Limited by the intrinsic properties of membrane materials, microparticles, colloidal particles, solute macromolecules or biological macromolecules in the material passing through the membrane will adsorb and deposit on the membrane surface or in the membrane pores, resulting in a decrease in membrane pore size or blockage, and ultimately leading to irreversible changes in the membrane permeation flux and separation characteristics, affecting the use efficiency and service life of the separation membrane. Among them, the adsorption of organic matter on the membrane surface is usually the main factor affecting membrane performance.
[0004] Research has confirmed that there is a positive relationship between the hydrophilicity of the membrane surface and the ability of the membrane to resist organic matter pollution. The stronger the hydrophilicity of the membrane surface, the smaller the adhesion ability of organic matter to the membrane surface. Therefore, improving the hydrophilicity of the membrane surface is an important measure to slow down membrane fouling.
[0005] At present, the effective strategies for improving the hydrophilicity of the membrane surface mainly include bulk blending modification and surface modification of the membrane. Bulk blending modification is to blend nanoparticles, small molecules or hydrophilic polymers with the membrane matrix to form a casting solution. Due to the presence of hydrophilic fillers, the hydrophilicity of the membrane surface is improved, and the anti-fouling ability of the membrane is effectively enhanced. Bulk blending modification has the advantages of simplicity, easy operation and low cost, but it also has the disadvantages of poor compatibility with the polymer matrix, uneven dispersion and easy loss. Coating a hydrophilic material onto the membrane surface by means of the van der Waals force or electrostatic force between the hydrophilic material and the membrane surface is a method of membrane surface modification. This method is simple to operate, no chemical reaction occurs, and the cost is relatively low. However, due to the weak interaction between the coating layer and the membrane surface, the hydrophilic functional layer peels off during use, resulting in the problem that the hydrophilic performance of the membrane surface is not long-lasting. Surface chemical grafting modification is a reliable method for membrane surface treatment. Since the hydrophilic material acts on the membrane surface through covalent bonds, the hydrophilic performance of the membrane is effectively maintained during use. Usually, the process of this method is relatively cumbersome, and in some cases, it will damage the intrinsic structure of the membrane, thus affecting the mechanical properties of the membrane.
[0006] Cellulose is a natural polymer material with abundant resource reserves and biodegradability. After removing the amorphous region of cellulose, highly crystalline nanocellulose (CNC) can be obtained. In recent years, with the development of degradable polymer composites, nanocellulose has attracted great attention. The inherent renewable, sustainable and environmentally friendly characteristics of CNC make it an ideal choice for the preparation of separation membranes. The surface of CNC has abundant hydroxyl groups (-OH), making it a highly hydrophilic material. Metal ions Ag + and Cu 2+ have antibacterial properties and are widely used in the research on the preparation of antibacterial membranes. However, there is no effective method in the existing technology to combine hydrophilic materials and antibacterial ions and act on the surface and pores of self-supporting ultrafiltration membranes.
[0007] Therefore, there is an urgent need for an anti-biofouling polyethersulfone self-supporting ultrafiltration membrane that can combine hydrophilic materials and antibacterial ions and act on the surface and pores of the membrane material, thereby having excellent anti-fouling and hydrophilic properties. Summary of the Invention
[0008] Object of the Invention: Aiming at the defects of the existing technology, the object of the present invention is to provide an anti-biofouling polyethersulfone self-supporting ultrafiltration membrane that can combine hydrophilic materials and antibacterial ions and act on the surface and pores of the membrane material, thereby having excellent anti-fouling and hydrophilic properties, and its preparation method and application.
[0009] Technical Solution: On the one hand, the present invention provides an anti-biofouling polyethersulfone self-supporting ultrafiltration membrane, which is prepared by fixing cellulose nanocrystals and antibacterial ions on the surface and pores of the polyethersulfone membrane through polyphenol monomers.
[0010] In the present invention, through the introduction of polyphenol monomers, on the one hand, it plays a role in immobilizing cellulose nanocrystals on the surface and pores of the membrane, and on the other hand, it provides an anchoring site for antibacterial nanomaterials, endowing the polyethersulfone membrane with excellent antibacterial properties.
[0011] Furthermore, the pore size of the ultrafiltration membrane is 30 - 100 nm, and the water contact angle is 25 - 40°.
[0012] The anti-biofouling polyethersulfone self-supporting ultrafiltration membrane provided by the present invention has excellent hydrophilic ability and can effectively carry out water treatment or biological material treatment.
[0013] On the other hand, the present invention provides a preparation method for the above-mentioned anti-biofouling polyethersulfone self-supporting ultrafiltration membrane, including the following steps: (1) Preparation of cellulose nanocrystals: After fragmenting the cellulose pulp board, add inorganic strong acid for acidification. After mechanical stirring under heating conditions, dilute with water. Add inorganic strong base solution to adjust the pH of the reaction system to 6.5 - 7.5. After washing with deionized water, centrifugal separation, and freeze-drying, cellulose nanocrystal powder is obtained; (2) Preparation of polyethersulfone primary ultrafiltration membrane: Dissolve polyethersulfone resin in a solvent, add a pore-forming agent, and stir in an oil bath to obtain a uniform casting solution. After cooling, degassing, and scraping the solution on a glass plate, place the glass plate in a coagulation bath. After the casting solution is peeled off from the glass plate, the polyethersulfone primary ultrafiltration membrane is obtained; (3) Preparation of anti-biofouling polyethersulfone self-supporting ultrafiltration membrane: Dissolve the cellulose nanocrystal powder obtained in step (1) in pure water, perform ultrasonic treatment, and prepare an aqueous solution of cellulose nanocrystals. After filtering through the polyethersulfone primary ultrafiltration membrane obtained in step (2), weigh polyphenol monomers in a buffer solution with a pH of 8 - 9. Place this solution on the surface of the filtered polyethersulfone membrane, and at the same time add inorganic salts and oxidants. After contact, remove the solution, and wash the polyethersulfone membrane with pure water to obtain the anti-biofouling polyethersulfone self-supporting ultrafiltration membrane.
[0014] Further, the raw material of the cellulose pulp board in step (1) is selected from at least one of wood, cotton, wheat straw, flax, or waste paper; The inorganic strong acid is selected from at least one of sulfuric acid, hydrochloric acid, or phosphoric acid aqueous solution, and the inorganic strong base is selected from at least one of lithium hydroxide, sodium hydroxide, or potassium hydroxide aqueous solution. The concentration of the inorganic strong acid and the inorganic strong base is 5 - 15 mol / L; In the acidification process, the solid-liquid ratio is 0.1 - 0.5, and the temperature is 40 - 60 °C.
[0015] For example, in the acidification process, the solid-liquid ratio can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5; The temperature can be 40 °C, 45 °C, 50 °C, 55 °C, 60 °C.
[0016] Further, the length of the cellulose nanocrystal powder obtained in step (1) is 50 - 100 nm, and the diameter is 5 - 10 nm.
[0017] Further, the solvent of the polyethersulfone resin in step (2) is a strongly polar aprotic solvent; The pore-forming agent is selected from at least one of acetone, ethanol, isopropanol, acetic acid, sodium chloride, sodium sulfate, calcium carbonate, sodium dodecyl sulfate, polylactic acid, or polycaprolactone; The coagulation bath is carried out in pure water at 25 - 40 °C.
[0018] For example, the strongly polar aprotic solvent can be at least one of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide.
[0019] Further, based on the total mass fraction of 100%, the mass percentage of each component in the homogeneous casting solution in step (2) is as follows: Polyethersulfone resin: 15 - 25% Pore former: 1 - 20% The balance is solvent.
[0020] For example, the mass percentage of polyethersulfone resin in the homogeneous casting solution can be 15%, 17.5%, 20%, 22.5%, 25%; The mass percentage of pore former can be 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%.
[0021] Further, the concentration of the aqueous solution of cellulose nanocrystals in step (3) is 0.05 - 0.3 g / L; The polyphenol monomer is selected from at least one of compounds containing catechol structure, the inorganic salt is selected from one of silver nitrate or copper sulfate, and the oxidant is selected from at least one of NaBH 4 or hydrogen peroxide; The addition amounts of the polyphenol monomer, inorganic salt and oxidant in the buffer solution are 1 - 5 g / L, 1 - 20 mmol / L, 2 - 100 mmol / L respectively; the contact time is 5 - 120 min.
[0022] For example, the addition amount of the polyphenol monomer in the buffer solution can be 1 g / L, 2 g / L, 3 g / L, 4 g / L, 5 g / L; The addition amount of the inorganic salt in the buffer solution can be 1 mmol / L, 3 mmol / L, 5 mmol / L, 8 mmol / L, 10 mmol / L, 12 mmol / L, 15 mmol / L, 18 mmol / L, 20 mmol / L; The addition amount of the oxidant in the buffer solution can be 2 mmol / L, 5 mmol / L, 10 mmol / L, 20 mmol / L, 30 mmol / L, 40 mmol / L, 50 mmol / L, 60 mmol / L, 70 mmol / L, 80 mmol / L, 90 mmol / L, 100 mmol / L.
[0023] For example, the buffer solution can be a weakly basic buffer solution of tris(hydroxymethyl)aminomethane-hydrochloric acid (Tris-HCl) with a concentration of 50 - 100 mM.
[0024] Further, the contact time is 60 - 120 min.
[0025] For example, the contact time can be 60 min, 75 min, 90 min, 105 min, or 120 min.
[0026] In the present invention, a suction filtration method is adopted to physically fix cellulose nanocrystals on the membrane surface and within the membrane pores, ensuring that the entire medium of the membrane surface and membrane pores is hydrophilic.
[0027] Further, the polyphenol monomer is selected from at least one of dopamine, dopa, tannic acid, catechol, or catechin compounds.
[0028] The present invention uses a polyphenol monomer to fix cellulose nanocrystals, ensuring the in-situ curing of cellulose nanocrystals on the membrane surface and within the membrane pores, avoiding the shedding of cellulose nanocrystals during the use of the membrane, and ensuring the durability of the anti-fouling performance of the membrane loaded with cellulose nanocrystals.
[0029] Finally, the present invention also provides the application of any one of the above anti-biofouling polyethersulfone self-supporting ultrafiltration membranes in water treatment or biological material treatment.
[0030] Beneficial effects: 1. The anti-biofouling polyethersulfone self-supporting ultrafiltration membrane provided by the present invention is prepared by fixing cellulose nanocrystals and antibacterial ions on the polyethersulfone membrane surface and within the membrane pores through a polyphenol monomer, which can stably load hydrophilic materials and antibacterial materials, thereby enabling the ultrafiltration membrane to have excellent hydrophilic properties and anti-biofouling capabilities, and making it applicable in the fields of water treatment or biological material treatment efficiently and stably.
[0031] 2. In the preparation method of the anti-biofouling polyethersulfone self-supporting ultrafiltration membrane provided by the present invention, a suction filtration method is adopted to physically fix cellulose nanocrystals on the membrane surface and within the membrane pores, ensuring that the entire medium of the membrane surface and membrane pores is hydrophilic.
[0032] 3. In the preparation method of the anti-biofouling polyethersulfone self-supporting ultrafiltration membrane provided by the present invention, a polyphenol monomer is used to fix cellulose nanocrystals, ensuring the in-situ curing of cellulose nanocrystals on the membrane surface and within the membrane pores, avoiding the shedding of cellulose nanocrystals during the use of the membrane, and ensuring the durability of the anti-fouling performance of the membrane loaded with cellulose nanocrystals.
[0033] 4. For the anti-biofouling polyethersulfone self-supporting ultrafiltration membrane provided by the present invention, through the introduction of a polyphenol monomer, on the one hand, it plays a role in fixing cellulose nanocrystals on the membrane surface and within the membrane pores, and on the other hand, it provides an anchoring site for antibacterial nanomaterials, endowing the polyethersulfone membrane with excellent antibacterial properties. Description of the Drawings
[0034] Figure 1 The variation of the pure water flux recovery rate of the self-supporting polyethersulfone ultrafiltration membrane during the BSA enhanced fouling process, where the x-axis is the fouling time and the y-axis is the pure water flux recovery rate. Detailed implementation manners
[0035] The present invention will be described below in conjunction with specific implementation manners. It should be noted that the following examples are examples of the present invention, only for illustrating the present invention, and not for limiting the present invention. Without departing from the gist or scope of the present invention, other combinations and various improvements within the concept of the present invention can be made.
[0036] The polyethersulfone used is polyethersulfone of BASF brand (grade: E6020P); other raw materials without specified sources are conventional raw materials that can be purchased by those skilled in the art.
[0037] Example 1 An anti-biofouling polyethersulfone self-supporting ultrafiltration membrane is prepared by the following steps: (1) Weigh 10.0 g of corncob, crush it with a crusher, acidify it with 100 g of 65% (mass fraction) H 2 SO 4 at 50 °C in a constant temperature water bath with mechanical stirring for 2 h. After the reaction is completed, add water for dilution, adjust the reaction system to neutral with 5 mol / L NaOH solution, wash with deionized water, centrifuge, and freeze-dry to obtain 6.4 g of CNC powder; (2) Weigh 30.0 g of polyethersulfone and 10.0 g of acetic acid, dissolve them in 150 g of N,N-dimethylacetamide, dissolve at 60 °C in an oil bath for 24 h to obtain a homogeneous casting solution. After cooling to room temperature, degas under vacuum for 3 h. Slowly pour the casting solution onto a glass plate, and scrape the film evenly with a 250 μm blade. Then place the glass plate coated with the casting solution in pure water at 40 °C. After the casting solution peels off from the glass plate, a self-supporting polyethersulfone ultrafiltration membrane is obtained; (3) Weigh 0.075 g of CNC and dissolve it in 0.5 L of pure water, sonicate to obtain a 0.15 g / L CNC aqueous solution. Fix the polyethersulfone membrane in a membrane cell, filter by suction. Prepare a Tris-HCl aqueous solution containing 5 mmol of CuSO 4 、20 mmol H 2 O 2 、2 g of dopamine hydrochloride, adjust the pH to 8.5, pour this solution onto the surface of the polyethersulfone membrane after CNC suction filtration, place it on a shaker for 60 min, then remove the buffer solution, wash the polyethersulfone membrane with pure water to obtain an anti-biofouling polyethersulfone self-supporting ultrafiltration membrane.
[0038] Example 2 An anti-biofouling polyethersulfone self-supporting ultrafiltration membrane is prepared by the following steps: Steps (1) and (2) are the same as those in Example 1; Step (3) is changed to weigh 0.15 g of CNC and dissolve it in 0.5 L of pure water, and ultrasonicate to obtain a 0.3 g / L CNC aqueous solution. Fix the polyethersulfone membrane in the membrane cell, filter by suction, and prepare a 1 L Tris-HCl aqueous solution containing 5 mmol of CuSO 4 、20 mmol of H 2 O 2 、2 g of dopamine hydrochloride. Adjust the pH to 8.5, pour this solution onto the surface of the polyethersulfone membrane after CNC suction filtration, place it on a shaker for 60 min, then remove the buffer solution, and wash the polyethersulfone membrane with pure water to obtain the anti-biofouling polyethersulfone self-supporting ultrafiltration membrane.
[0039] Example 3 An anti-biofouling polyethersulfone self-supporting ultrafiltration membrane is prepared by the following steps: Steps (1) and (2) are the same as those in Example 1; Step (3) is changed to weigh 0.15 g of CNC and dissolve it in 0.5 L of pure water, and ultrasonicate to obtain a 0.3 g / L CNC aqueous solution. Fix the polyethersulfone membrane in the membrane cell, filter by suction, and prepare a 1 L Tris-HCl aqueous solution containing 5 mmol of CuSO 4 、20 mmol of H 2 O 2 、2 g of dopamine hydrochloride. Adjust the pH to 8.5, pour this solution onto the surface of the polyethersulfone membrane after CNC suction filtration, place it on a shaker for 120 min, then remove the buffer solution, and wash the polyethersulfone membrane with pure water to obtain the anti-biofouling polyethersulfone self-supporting ultrafiltration membrane.
[0040] Example 4 An anti-biofouling polyethersulfone self-supporting ultrafiltration membrane is prepared by the following steps: Steps (1) and (3) are the same as those in Example 1; Step (2) is changed to weigh 36.0 g of polyethersulfone and 12.0 g of acetic acid and dissolve them in 150 g of N,N-dimethylacetamide, dissolve in an oil bath at 60 °C for 24 h to obtain a homogeneous casting solution. After cooling to room temperature, degas under vacuum for 3 h, slowly pour the casting solution onto a glass plate, and scrape the film evenly with a 250 μm doctor blade. Then place the glass plate coated with the casting solution in pure water at 40 °C. After the casting solution peels off from the glass plate, obtain the self-supporting polyethersulfone ultrafiltration membrane.
[0041] Comparative Example 1 An anti-biofouling polyethersulfone self-supporting ultrafiltration membrane is prepared by the following steps: Steps (1) and (2) are the same as in Example 1; Step (3) is changed to weighing 0.15 g of CNC and dissolving it in 0.5 L of pure water, followed by ultrasonic treatment to obtain a 0.3 g / L aqueous solution of CNC. Fix the polyethersulfone membrane in the membrane cell, perform suction filtration, and prepare a 1 L Tris-HCl aqueous solution containing 20 mmol H 2 O 2 and 2 g of dopamine hydrochloride. Adjust the pH to 8.5, pour this solution onto the surface of the polyethersulfone membrane after suction filtration of CNC, place it on a shaker for 1 h, then remove the buffer solution, and wash the polyethersulfone membrane with pure water to obtain an anti-biofouling polyethersulfone self-supporting ultrafiltration membrane.
[0042] Comparative Example 2 An anti-fouling polyethersulfone self-supporting ultrafiltration membrane is prepared by the following steps: Steps (1) and (2) are the same as in Example 1; Step (3) is changed to weighing 0.15 g of CNC and dissolving it in 0.5 L of pure water, followed by ultrasonic treatment to obtain a 0.3 g / L aqueous solution of CNC. Fix the polyethersulfone membrane in the membrane cell, perform suction filtration to obtain an anti-fouling polyethersulfone self-supporting ultrafiltration membrane.
[0043] Comparative Example 3 A polyethersulfone self-supporting ultrafiltration membrane is prepared by the following steps: Weigh 30.0 g of polyethersulfone and 10.0 g of acetic acid and dissolve them in 150 g of N,N-dimethylacetamide. Dissolve for 24 h in an oil bath at 60 °C to obtain a homogeneous casting solution. After cooling to room temperature, perform vacuum degassing for 3 h. Slowly pour the casting solution onto a glass plate, and use a 250 μm doctor blade to uniformly scrape the film. Then place the glass plate coated with the casting solution in pure water at 40 °C. After the casting solution peels off from the glass plate, obtain a self-supporting polyethersulfone ultrafiltration membrane.
[0044] Performance testing Pore size testing: The pore sizes of the polyethersulfone self-supports prepared in steps (2) and (3) of Examples 1-4 and Comparative Examples 1-2 and Comparative Example 3 are tested by the gas-liquid displacement method. The wetting liquid is Porefil, and the test results are shown in Table 1.
[0045] Table 1 Pure water contact angle testing: The pure water contact angles of the polyethersulfone self-supports prepared in steps (2) and (3) of Examples 1-4 and Comparative Examples 1-2 and Comparative Example 3 are tested respectively. The test results are shown in Table 2.
[0046] Table 2 According to the comparison of the test results in Table 1 and Table 2, the anti-biofouling polyethersulfone self-supporting ultrafiltration membrane provided by the present invention has excellent hydrophilic ability. After passing CNC through the membrane, fixing polyphenol monomers and loading antibacterial ions, it can effectively reduce the contact angle on the surface of the ultrafiltration membrane and improve hydrophilicity.
[0047] Dynamic anti-fouling performance test: The dynamic anti-fouling performance tests were carried out on the polyethersulfone self-supporting ultrafiltration membranes prepared in Examples 1-4 and Comparative Examples 1-3 respectively.
[0048] Process of dynamic anti-fouling performance test: The cross-flow membrane sheet detection platform was used for detection. First, the initial stable flux was tested with pure water. Then, under the test conditions of an aqueous solution of 300 ppm BSA, an operating pressure of 1.0 bar, a temperature of 25 °C, and a pH value of 6.5 - 7.5, after running for 8 hours, it was rinsed with pure water for 10 min, the pure water stable flux was tested, the flux recovery rate was calculated, and the test was repeated 3 times. The obtained results are shown in Figure 1 。
[0049] According to Figure 1 the comparison of the test results, the anti-biofouling polyethersulfone self-supporting ultrafiltration membrane provided by the present invention has an excellent pure water flux recovery rate and can be stably applied in the field of water treatment for a long time.
[0050] Antibacterial performance test: It was detected by the static bacteria culture method. Gram-negative bacteria ( E.coli ) and Gram-positive bacteria ( B.subtilis ) were cultured in LB culture medium at 37 °C for 18 h until the logarithmic growth phase of bacteria was reached (the formula of LB culture medium is: tryptone 10 g / L, yeast extract 5 g / L, sodium chloride 10 g / L, PH 7.4). The membrane sheets (2.6×7.6 cm) of Examples 1-4 and Comparative Examples 1-3 were placed in a sterile petri dish and sterilized under ultraviolet irradiation for 30 min; 60 μL of bacterial suspension (concentration about 1.0×10 6 CFU / mL, the dispersion medium is physiological saline) was evenly coated on the membrane surface, and a cover glass was covered to make the bacterial liquid completely spread; after the membrane sheet was incubated in a 37 °C constant temperature incubator for 3 h, 9 mL of physiological saline was used to collect the bacteria on the membrane surface and the cover glass, and 1 mL of it was evenly mixed with nutrient agar; after the petri dish was cultured at 37 °C for 48 h, the colonies were counted and the antibacterial rate was calculated. The test results are shown in Table 3.
[0051] Table 3 According to the test results in Table 3, the anti-biofouling polyethersulfone self-supporting ultrafiltration membrane provided by the present invention passes through Cu 2+During the process of fixing PDA to CNC, it is fixed on the membrane, showing good antibacterial effects against both Gram-negative and Gram-positive bacteria and having excellent anti-biofouling ability.
[0052] The above embodiments are only for illustrating the technical concept and characteristics of the present invention, and the purpose is to enable those who are familiar with this technology to understand the content of the present invention and implement it. However, it cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit and essence of the present invention should be covered within the protection scope of the present invention.
Claims
1. A polyethersulfone self-supporting ultrafiltration membrane resistant to biological contamination, characterized in that: The ultrafiltration membrane is prepared by fixing cellulose nanocrystals and antibacterial ions on the surface and in the membrane pores of a polyethersulfone membrane through polyphenol monomers.
2. The anti-biological contamination polyethersulfone self-supporting ultrafiltration membrane according to claim 1, characterized in that: The pore size of the ultrafiltration membrane is 30-100 nm, and the water contact angle is 25-40°.
3. The method for preparing the polyethersulfone self-supporting ultrafiltration membrane resistant to biological contamination according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Preparation of cellulose nanocrystals: After the cellulose pulp is fragmented, an inorganic strong acid is added for acidification, and the mixture is mechanically stirred under heating conditions and diluted with water. An inorganic strong base solution is added to adjust the pH of the reaction system to 6.5-7.5, and the cellulose nanocrystal powder is obtained after washing with deionized water, centrifugal separation, and freeze-drying. (2) Preparation of polyethersulfone primary ultrafiltration membrane: dissolving polyethersulfone resin in a solvent, adding a porogen and stirring in an oil bath to obtain a uniform casting solution, cooling, degassing, and scraping the film on a glass plate, placing the glass plate in a coagulation bath, and after the casting solution is peeled off from the glass plate, a polyethersulfone primary ultrafiltration membrane is obtained; (3) Preparation of a polyethersulfone self-supporting ultrafiltration membrane resistant to biological contamination: The cellulose nanocrystal powder of step (1) is dissolved in pure water, subjected to ultrasonic treatment, and then prepared into a cellulose nanocrystal aqueous solution. After suction filtration through the polyethersulfone primary ultrafiltration membrane of step (2), polyphenol monomers are weighed in a buffer solution of pH 8-9, and the solution is placed on the surface of the polyethersulfone membrane after suction filtration. At the same time, an inorganic salt and an oxidant are added. After contact, the solution is removed, and the polyethersulfone membrane is washed with pure water to obtain the polyethersulfone self-supporting ultrafiltration membrane resistant to biological contamination.
4. The method for preparing the polyethersulfone self-supporting ultrafiltration membrane resistant to biological contamination according to claim 3, characterized in that: The raw material of the cellulose pulp board in step (1) is selected from at least one of wood, cotton, wheat straw, flax or waste paper; The inorganic strong acid is selected from at least one of sulfuric acid, hydrochloric acid or phosphoric acid aqueous solution, the inorganic strong base is selected from at least one of lithium hydroxide, sodium hydroxide or potassium hydroxide aqueous solution, and the concentration of the inorganic strong acid and the inorganic strong base is 5-15 mol / L; The solid-liquid ratio during the acidification process is 0.1-0.5 and the temperature is 40-60°C.
5. The method for preparing the polyethersulfone self-supporting ultrafiltration membrane resistant to biological contamination according to claim 3, characterized in that: The cellulose nanocrystal powder obtained in step (1) has a length of 50-100 nm and a diameter of 5-10 nm.
6. The method for preparing the polyethersulfone self-supporting ultrafiltration membrane resistant to biological contamination according to claim 3, characterized in that: The solvent of the polyethersulfone resin in step (2) is a highly polar aprotic solvent; The porogen is selected from at least one of acetone, ethanol, isopropanol, acetic acid, sodium chloride, sodium sulfate, calcium carbonate, sodium dodecyl sulfate, polylactic acid or polycaprolactone; The coagulation bath is carried out in pure water at 25-40°C.
7. The method for preparing the polyethersulfone self-supporting ultrafiltration membrane resistant to biological contamination according to claim 3, characterized in that: Taking the total mass fraction as 100%, the mass percentage of each component in the uniform casting solution in step (2) is: Polyethersulfone resin 15-25% Porogen 1-20% The balance is solvent.
8. The method for preparing the polyethersulfone self-supporting ultrafiltration membrane resistant to biological contamination according to claim 3, characterized in that: The concentration of the cellulose nanocrystal aqueous solution in step (3) is 0.05-0.3 g / L; The polyphenol monomer is selected from at least one of compounds containing a catechol structure, the inorganic salt is selected from one of silver nitrate and copper sulfate, and the oxidant is selected from at least one of sodium borohydride and hydrogen peroxide; The added amounts of the polyphenol monomer, inorganic salt and oxidant in the buffer solution are 1-5 g / L, 1-20 mmol / L and 2-100 mmol / L respectively; and the contact time is 5-120 min.
9. The method for preparing the polyethersulfone self-supporting ultrafiltration membrane resistant to biological contamination according to claim 8, characterized in that: The polyphenol monomer is selected from at least one of dopamine, dopa, tannic acid, catechol or catechin compounds.
10. Use of the polyethersulfone self-supporting ultrafiltration membrane resistant to biological fouling according to any one of claims 1 to 2 in water treatment or biological material treatment.
Citation Information
Patent Citations
Preparation method and application of nano microcrystalline cellulose / dopamine composite film
CN111001314A
Two-step modified composite nanofiltration membrane containing cellulose nanocrystal intermediate layer and dopamine in-situ modified layer and preparation method thereof
CN112452164A
New method for regulating and controlling membrane combined pollution based on synergistic effect of nano materials
CN112619428A
Polyamide composite reverse osmosis membrane with biological pollution resistance and preparation method thereof
CN114053875A
High flux microfiltration membranes with virus and metal ion adsorption capability for liquid purification
US20130180917A1
Cited By
Internal pressure type polyether sulfone hollow fiber ultrafiltration membrane as well as preparation method and application thereof
CN121466843A